Confirmation of a new breeding area for humpback whales (Megaptera novaeangliae) in the central South Pacific - Irving, R. A.; O'Keefe, S.; Warren, P.; Koldewey, H. J.; Dawson, T. P. (J. Cetacean Res. Manage., 2023)
Small numbers of humpback whales (Megaptera novaeangliae, Borowski 1781) have been visiting Pitcairn Island in the central South Pacific annually since the early 1990s. The whales have been observed between the months of June and November in mixed groups including adult males, mothers with calves and escort whales. More recently, similar small groups have also been observed at neighbouring Henderson Island, 200km ENE of Pitcairn. The sightings of mothers with very young calves, the observations of surface-active behaviours and the witnessing of (unrecorded) singing bouts, strongly suggest that the waters around these two islands are being used as calving and mating habitats during the austral winter and spring. Recent photographs and videos taken during visits to both islands confirm that calves are of a size that would suggest they have been born at either Pitcairn or Henderson Islands. Further work is required to assess how these small breeding whale groups may relate to larger groups further west, centered on Mo’orea and Rurutu in French Polynesia, which constitute part of the Cook Islands-French Polynesia Breeding Stock F. As no identification of individuals has yet been undertaken at the Pitcairn Islands, it is too early to determine whether there is any exchange of individuals with these more established groups.